2021
DOI: 10.3389/fgene.2020.576260
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Changes Are Rapid Responses of the Genome to the Newly Synthesized Autotetraploid Carassius auratus

Abstract: Whole genome duplication events have occurred frequently during the course of vertebrate evolution. To better understand the influence of polyploidization on the fish genome, we herein used the autotetraploid Carassius auratus (4n = 200, RRRR) (4nRR) resulting from the whole genome duplication of Carassius auratus (2n = 100, RR) (RCC) to explore the genomic and epigenetic alterations after polyploidization. We subsequently performed analyses of full-length transcriptome dataset, amplified fragment length polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Recent studies have uncovered rapid genomic and genetic changes and epigenetic alterations in autotetraploid Carassius auratus ( Huang et al, 2020 ; Wang et al, 2020 ). Nevertheless, the molecular mechanism of reproductive property that diploid gametogenesis and maintenance of fertility have been noticed is rarely indicated but necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have uncovered rapid genomic and genetic changes and epigenetic alterations in autotetraploid Carassius auratus ( Huang et al, 2020 ; Wang et al, 2020 ). Nevertheless, the molecular mechanism of reproductive property that diploid gametogenesis and maintenance of fertility have been noticed is rarely indicated but necessary.…”
Section: Introductionmentioning
confidence: 99%
“…A study of rice showed that ploidy (diploid to haploid and diploid to triploid) affects CHH methylation frequency [ 20 ]. The autotetraploid fish genome of Carassius auratus exhibited a lower genome-wide DNA methylation level than diploid fish [ 21 ]. A small-scale study on brown trout detected only 408 methylation loci and no difference in methylation between tripods and diploid fish [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study on rice showed that ploidy (diploid to haploid and diploid to triploid) affects CHH methylation frequency [20]. The autotetraploid sh genome of Carassius auratus exhibited a lower genome-wide DNA methylation level than diploid sh [21]. A smallscale study on brown trout detected only 408 methylation loci and detected no difference in methylation between tripods and diploid sh [22].…”
Section: Introductionmentioning
confidence: 99%